1990
DOI: 10.7863/jum.1990.9.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Graded compression ultrasound in the diagnosis of appendicitis. A comparison of diagnostic criteria.

Abstract: Four sonographic diagnostic criteria for appendicitis, (1) any visualization, (2) appendiceal diameter greater than 6.0 mm, (3) muscular wall thickness greater than or equal to 3.0 mm, and (4) presence of a complex mass, were compared in a series of 200 patients clinically suspected of having appendicitis. The diagnosis of appendicitis was confirmed histopathologically and included all forms of appendicitis with mucosal invasion by inflammatory cells. The sensitivities of all the criteria were low (11% to 75%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…We evaluated the diagnostic performance of the size of the appendix using a receiver operator curve (Fig. 4) and found that a size threshold of 7.5 mm provided the best balance between sensitivity and specificity, which is slightly higher than our initial size threshold of 6.0 mm [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the diagnostic performance of the size of the appendix using a receiver operator curve (Fig. 4) and found that a size threshold of 7.5 mm provided the best balance between sensitivity and specificity, which is slightly higher than our initial size threshold of 6.0 mm [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…Since then, this technique has become standard in studies of sonographic investigation of acute appendicitis, and high levels of sensitivity and specificity have been achieved in the diagnosis of this disease [5][6][7][8][9][10][11]. Although several authors report that compression at sonography is usually well tolerated [12,13] for children who have rebound tenderness with appendicitis, gentle percussion is recommended even at physical examination to make the examination less painful [14].…”
mentioning
confidence: 99%
“…4 In most of the cases that valorize the contribution of US into the diagnosis of the acute appendicitis the sensitivity is from 75-90%, and specificity is from 86-100% and the diagnostic accuracy is from 87-96%. 1,3,6,7,14,15 Most of the newly publications demonstrated that the greatest diameter of the appendix is >6mm, there is about inflammation in 93% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…In 30% of the cases the appendix could be hidden from the anterior peritoneum due to its pelvic or retro colic location. 6 The poster lateral approach is better for the exploration of the retrocecal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation